Effect of Heat Stress on Thermoregulatory Response of Murrah and Nili Ravi Buffaloes in the Subtropical Region of India - Gupta, Deesha; Narang, Raman; Desmukh, Bharti; Malhotra, Puneet; Narang, Deepti (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Present study was conducted on the effects of thermal stress on adult Murrah and Nili- Ravi buffaloes (n=96). Using the temperature  humidity index (THI), the thermal stress was calculated. THI was significantly (P
Keywords: Temperature Humidity Index, Heat stress, Buffalo, Respiration rate, Murrah.